A new phenolic glycoside from Trollius chinensis Bunge with anti-inflammatory and antibacterial activities. Issue 13 (1st July 2022) - Feng, Jie; Zhao, Danyang; Xu, Qiannan; Liu, Xiangzhong; Zhou, Mi; Ye, Xiansheng; Lin, Ting; Wang, Guanghui; Sun, Cuiling; Ding, Rong; Tian, Wenjing; Chen, Haifeng
Abstract: A undescribed phenolic glycoside, trochinenol A (1 ), was isolated from the flowers of Trollius chinensis Bunge and the structure was identified by spectroscopic methods. Its anti-inflammatory and antibacterial effects were investigated by broth microdilution and NF-κB reporter gene assays. Consequently, compound 1 exhibited an appreciable effect against Staphylococcus aureus with the MIC value of 6.25 µg/mL. Besides, it showed moderate effect against TNFα-induced activation of NF-κB pathway. Graphical Abstract: UF0001